2002
DOI: 10.1152/jn.00365.2001
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization of Glycine-Gated Chloride Currents Recorded in Rat Hippocampal Slices

Abstract: Chattipakorn, Siriporn C. and Lori L. McMahon. Pharmacological characterization of glycine-gated chloride currents recorded in rat hippocampal slices. J Neurophysiol 87: 1515-1525, 2002; 10.1152/jn. 00365.2001. An inhibitory role for strychnine-sensitive glycine-gated chloride channels (GlyRs) in mature hippocampus has been overlooked, largely due to the misconception that GlyR expression ceases early during development and to few functional studies demonstrating their presence. As a result, little is known r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
90
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(110 citation statements)
references
References 62 publications
(60 reference statements)
18
90
1
1
Order By: Relevance
“…Indeed, we found that endogenous accumulation of glycine by GlyT1 antagonists induced an STN-sensitive tonic current in CA1 pyramidal neurons ( Figure 5). The reported existence of GlyRs containing homomeric a2 subunits in the hippocampus (Chattipakorn and McMahon, 2002;Mori et al, 2002;Thio et al, 2003;Yoon et al, 1998) may underlie this tonic current. In general, functional consequences of the tonic inhibition are not well understood.…”
Section: Glycine Accumulation Reduces Overall Excitabilitymentioning
confidence: 91%
See 2 more Smart Citations
“…Indeed, we found that endogenous accumulation of glycine by GlyT1 antagonists induced an STN-sensitive tonic current in CA1 pyramidal neurons ( Figure 5). The reported existence of GlyRs containing homomeric a2 subunits in the hippocampus (Chattipakorn and McMahon, 2002;Mori et al, 2002;Thio et al, 2003;Yoon et al, 1998) may underlie this tonic current. In general, functional consequences of the tonic inhibition are not well understood.…”
Section: Glycine Accumulation Reduces Overall Excitabilitymentioning
confidence: 91%
“…The difference in half-maximal concentrations of glycine responses in hippocampus between single neuron and slice preparations suggests the existence of powerful reuptake mechanisms in slices (Chattipakorn and McMahon, 2002). To look for direct evidence of a role of GlyTs in tuning tonic activation of GlyRs in hippocampus, we studied the effect of sarcosine, a specific GlyT1 antagonist, on E-S coupling.…”
Section: Glyt1 But Not Glyt2 Antagonists Induced Stn-sensitive E-s Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Blocking of GLYT1 is known to enhance the activation of NMDA receptor-dependent synaptic transmission [17] and to reduce neuronal signaling [18,19]. Previous reports have suggested that Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, also in hippocampal tissue and cultured neurons GlyR 2 subunits are found in clusters, both synaptically and extrasynaptically (Brackmann et al 2004;Danglot et al 2004). Pharmacological and single channel analysis showed that in acutely prepared hippocampal slices GlyRs in interneurons and CA1 pyramidal cells are mostly homo-oligomeric, pictrotoxinin sensitive channels with larger single channel conduction states (>100 pS) whereas hetero-oligomeric, subunit containing GlyRs were found with lower frequency (10-20%) (Chattipakorn and McMahon 2002). Also in cultured hippocampal neurons 2 homo-olgomeric receptors, which were replaced by subunit containing GlyRs were observed (J. Kuhse, unpublished observation).…”
Section: Subunit Switch Assembly and Function Of Glyr Isoformsmentioning
confidence: 95%